The Importance of Education in Diabetic Foot Care of Patients with Diabetic Neuropathy - Şen, H. M.; Şen, H.; Aşık, M.; Özkan, A.; Binnetoglu, E.; Erbağ, G.; Karaman, H. I. Ö. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: Our aim is to research the effect of the knowledge and routine gained from the diabetic foot (DF) care education program given to patients with Type 2 Diabetes Mellitus (DM) with diabetic neuropathy.Materials and Method: A total of 104 patients with Type 2 DM and diabetic neuropathy participated in a survey to evaluate standards of DF care, and knowledge of and behavior relating to personal care. The difference in knowledge and personal care between the group who had received education on diabetes and the group who had not was researched.Results: A total of 42.3% of patients reported receiving education about diabetes. The education for Type 2 DM patients increased the frequency of attending yearly check-ups (p:0.028), and helped develop the habit of having doctors check their feet (p:0.004). When comparing the daily practice of those who had received education about DF care with those who had not, positive effects of education were seen in all questions evaluating foot care, nail care and choice of shoe. The statistical analysis proved that the educated group were significantly better in terms of foot care such as using moisturizer (p:0.002) and using insoles (p:0.042).Conclusion: Our study reveal that educating diabetic patients about foot care is an effective method to develop their knowledge. However we observed that this education is not provided to all diabetic patients. We believe that every diabetic patient should receive education from the moment of diagnosis and repeated education during check-ups by doctors will increase effectiveness.
Keywords: diabetes mellitus; neuropathy; diabetic foot; education